Microfluidic interfacial tensiometry - Hudson,SD; Cabral,JT; Goodrum,WJ; Beers,KL; Amis,EJ (Applied Physics Letters, 2005)
A microfluidic approach to measure interfacial tension σ of immiscible fluids rapidly is reported. This method rests upon quantitative real-time analysis of two-phase flow and drop-shape dynamics. Drops of prescribed dimension and spacing are produced, accelerated, and deformed under extensional flow. These measurements compare well with existing published data and demonstrate a wide range of accessible interfacial tension (e.g., from 2.5 to 60mNm).